Afrika und Ägypten : zwischen Cheikh Anta Diop und Jan Assmann - Die Schwierigkeiten einer Begegnung - Balz, Heinrich (Hans-Bonnet-Studien zur ägyptischen Religion, 2022)
When thinking about Africa, Pharaonic Egypt plays a special role. When dealing with Egypt, the African localization of its culture is a challenge. Heinrich Balz describes how Africa's impetuous grip on Egypt is to be understood and how Africa appears or does not appear in contemporary Egyptology. The starting point is Cheikh Anta Diop's work on the African origins of pharaonic culture. Its African reception is followed, for example, in the works of Théophile Obenga and Joseph Mabita Nkata, up to points of contact with Atlantic Afrocentrism. How Western Egyptology addresses the relationship between Africa and Egypt is discussed using the example of the cultural-historical works of Henri Frankfort and Jan Assmann. In an article, Martin Fitzenreiter draws the arc of the narrated memories of an African Egypt from antiquity to modern times of the nations of the Nile valley